The irrational offering of benzodiazepines by medicine shops in Bangladesh: Recommends implementation of retail pharmacy as soon as possible (Bangladesh Journal of Medical Science, 2018)
As controlled drugs, benzodiazepines are one of the most familiar prescription drugs. This present study was designed to determine the proportion of medicine shops that irrationally offered benzodiazepines without prescription in the Chittagong division of Bangladesh. A crosssectional study on the sample of 563 medicine shops was conducted from July 2015 to August 2015. A simulated client methodology was used to complete this survey. Among the total 539 medicine shops, 237(43.97%) medicine shops were offered benzodiazepines. On the other hand, 302(56.02%) medicine shops were denied to sell benzodiazepines. The offering of controlled drugs without the prescription was terrifyingly high by medicine shops in the Chittagong division. Thus, the responsible authority should be taken steps to overcome this irrationality.Bangladesh Journal of Medical Science Vol.17(1) 2018 p.175-177